Testing the Influence of Retail Cues on Consumer Purchase Interest in Grocery Stores - Sujeni Sujeni (Brilliant International Journal Of Management And Tourism, 2026)
Grocery stores remain an important retail outlet for the community because they are close by, easy to reach, and help meet daily needs. However, to maintain business continuity, store owners need to understand the factors that can drive consumer purchasing interest. This study aims to analyze the effect of price, product completeness, stock availability, and shopping convenience on consumer purchasing interest in grocery stores. The study used a quantitative approach with a survey method of 109 respondents selected using purposive sampling. Data were collected directly (offline) through a five- point Likert scale questionnaire and analyzed using SEM-PLS with the help of SmartPLS version 4. The results showed that shopping convenience had a positive and significant effect on purchasing interest (β = 0.203; p = 0.011), while price (p = 0.435), product completeness (p = 0.069), and stock availability (p = 0.104) did not have a significant effect. These findings imply that grocery store managers need to prioritize improving shopping convenience, such as maintaining cleanliness, neat layout, ease of finding items, and fast service, to increase consumer purchasing interest.